Wpływ relacji społecznych na pozycję rynkową polskich przedsiębiorstw - Daszkiewicz, Magdalena (The Influence of Community Relations on the Market Position of Polish Firms, 2007)
Competitive environment and the growing demands of the market make firms be more responsible in their activities. The aim of this article was to analyze influence of community relations on competitive advantage of firms. The article presents CSR (Corporate Social Responsibility) conception, emphasizing its importance for corporate position on the market. The author made an attempt to analyze the situation in the field of community relations on the Polish market. The empirical illustration of discussed problems comes from the results of the questionnaire research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 63-73